Hospital Rating Report 2006: Approaches to the sustainable financing of patient care and treatment. Development of German hospitals up to 2010 - Boris Augurzky; Dirk Engel; Sebastian Krolop; Christoph M. Schmidt; Stefan Terkatz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Health expenditures in Germany - as in almost all industrialized countries - grow more rapidly than the gross domestic product. Since a large portion of German health expenditures is financed by non-voluntary health premiums proportional to personal wages and collected by social health insurances, rising expenditures mean rising non-wage labor costs. This might trigger a vicious circle of rising non-wage labor costs and, as a consequence, rising unemployment which, in turn, reduces the number of payers to the social health insurances. To limit growth of health expenditures, German politics implemented budget constraints for some health care providers, especially for hospitals. Therefore, hospitals are under considerable strain to reduce their costs. Due to the demographic aging process and technical progress in health care, which tend to increase demand for health care services, expenditures are expected to rise above average while contributions to social health insurance remain constant at best. Given this situation it is of great importance to know more about the economic situation of German hospitals which have a market share in the health market of approximately 25% or roughly 60 billion euros in 2004. Therefore, we decided to update our first Hospital Rating Report, a joint work published by the Rheinisch-Westfälisches Institut für Wirtschaftsforschung Essen (RWI Essen) and the ADMED Health Care Consultancy. For this purpose we collected 277 annual financial statements of 347 hospitals for various years and additional information on their medical output. We aim at increasing the transparency in the German health system in order to improve the basis for decision makers in politics, for potential investors in the German health system, and for hospitals and their business partners. We calculate balance sheet ratings and probabilities of default for hospitals in a way similar to banks conducting credit ratings for their clients. This gives a good impression of the financial stability of German hospitals. Basically, we would be able to name the hospitals and their ratings. However, we decided against doing so because balance sheet rating is only part of a full rating process - though a very important one. Instead, we compare ratings across selected subgroups of German hospitals and build financial forecasts up to 2010. The next edition of the Hospital Rating Report, to be published in January 2007, will additionally contain benchmarking data of selected subgroups and considerably more regional aspects of the results given in this report.
urn:nbn:de:101:1-200910202060
Keywords: 330